Genetic conjugation of components in two pneumococcal fusion protein vaccines enhances paediatric mucosal immune responses. Issue 14 (30th March 2015) - Pope, Caroline; Oliver, Elizabeth H.; Ma, Jiangtao; Langton Hewer, Claire; Mitchell, Tim J.; Finn, Adam
Highlights: A new, affordable pneumococcal vaccine offering broader protection is needed. Fusion of PsaA to Δ6Ply enhances CD4+ T-cell responses in children's nasopharynges. CD4+ T-cell responses had a Th1/Th17 cytokine profile. Membrane binding activity of Ply/Δ6Ply may confer valuable adjuvant properties. Non-toxic pneumolysoids may be suitable for inclusion in future vaccines. Abstract: Streptococcus pneumoniae colonises the upper respiratory tract and can cause pneumonia, meningitis and otitis media. Existing pneumococcal conjugate vaccines are expensive to produce and only protect against 13 of the 90+ pneumococcal serotypes; hence there is an urgent need for the development of new vaccines. We have shown previously in mice that pneumolysin (Ply) and a non-toxic variant (Δ6Ply) enhance antibody responses when genetically fused to pneumococcal surface adhesin A (PsaA), a potentially valuable effect for future vaccines. We investigated this adjuvanticity in human paediatric mucosal primary immune cell cultures. Adenoidal mononuclear cells (AMNC) from children aged 0–15 years ( n  = 46) were stimulated with conjugated, admixed or individual proteins, cell viability and CD4+ T-cell proliferative responses were assessed using flow cytometry and cytokine secretion was measured using multiplex technology. Proliferation of CD4+ T-cells in response to PsaAPly, was significantly higher than responses to individual or admixed proteins ( p  = 0.002). In contrast, an enhanced response to PsaAΔ6Ply compared to individual or admixed proteins only occurred at higher concentrations ( p  < 0.01). Evaluation of cytotoxicity suggested that responses occurred when Ply-induced cytolysis was inhibited, either by fusion or mutation, but importantly an additional toxicity independent immune enhancing effect was also apparent as a result of fusion. Responses were MHC class II dependent and had a Th1/Th17 profile. Genetic fusion of Δ6Ply to PsaA significantly modulates and enhances pro-inflammatory CD4+ T-cell responses without the cytolytic effects of some other pneumolysoids. Membrane binding activity of such proteins may confer valuable adjuvant properties as fusion may assist Δ6Ply to deliver PsaA to the APC surface effectively, contributing to the initiation of anti-pneumococcal CD4+ T-cell immunity.